M. Joannes Neunachbar. Elbingensis. Ecclesiar. Torun. Senior. / Jacob Sandrart. - Sandrart, Jacob von (1630-1708) (1660)
Przedstawia portret w ujęciu 3/4, przy stole, na tle biblioteki Johannes Neunachbar (1624-1680).